Post-marketing surveillance of anti-malarial medicines used in Malawi - Chikowe, I.; Osei-Safo, D.; Harrison, J.J.; Konadu, D.Y.; Addae-Mensah, I. (My University, 2015)
Abstract Background The growing concern over the extent of anti-malarial medicine resistance in sub-Saharan Africa, driven largely by administration of sub-therapeutic doses derived from falsified and substandard medicines necessitates regular monitoring of the quality of these medicines to avert any potential public health disaster. This study aimed at determining the active pharmaceutical ingredient (API) content of anti-malarial medicines available in Malawi with respect to the manufacturers’ label claim and pharmacopoeia specifications. Methods Samples of anti-malarial medicines (112) collected from both licensed and unlicensed markets throughout Malawi were subjected to visual inspection of dosage form and packaging, and registration verification with the regulatory body. Basic (colourimetric) tests were employed to establish the presence and identity of the requisite APIs. Semi-quantitative thin layer chromatography (SQ-TLC) was employed as a quick assay for the verification of identity and estimation of the API content while HPLC assays were used to quantify the APIs. The results were compared with pharmacopoeia specifications and manufacturers’ label claims. For combination therapies, a sample was considered to have failed if one or more of its component APIs did not meet pharmacopoeia specifications. Results There was 86.6% registration status and 100% compliance with visual inspection and basic tests confirming the presence of requisite APIs. The identification test was confirmed by the SQ-TLC assay. API quantification by HPLC assay however, showed that 88.4% (99/112) of the samples failed the quality tests due to the presence of either insufficient or excessive API. Conclusions The results suggest the existence of substandard anti-malarial medicines in Malawi. The presence of both excessive and insufficient artemisinin-based and non-artemisinin-based API, clearly points to poor adherence to GMP and improper handling during storage or distribution. The country relies heavily on imported anti-malarial medicines so there is an urgent need to carry out regular and thorough post-market surveillance of medicines to ensure better quality health care delivery.